2021
DOI: 10.1128/msystems.00046-21
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Transcriptomic Analysis of Microviridae φX174 Infection Reveals Broad Upregulation of Host Escherichia coli Membrane Damage and Heat Shock Responses

Abstract: Measuring host-bacteriophage dynamics is an important approach to understanding bacterial survival functions and responses to infection. The model Microviridae bacteriophage φX174 is endemic to the human gut and has been studied for over 70 years, but the host response to infection has never been investigated in detail. To address this gap in our understanding of this important interaction within our microbiome, we have measured host Escherichia coli C proteomic and transcriptomic response to φX174 infection. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 97 publications
(121 reference statements)
1
18
1
Order By: Relevance
“…Bacteriophage ϕX174 is a small, icosahedral, and non-tailed virus belonging to Microviridae (23) and work has shown that mutations in DnaJ/DnaK/GrpE/GroEL/GroES make the E. coli host more sensitive to lysis by E protein (24). In addition to this work, we have recently shown that the small heat shock proteins (sHsps) IbpA and IbpB were the most upregulated host proteins during ϕX174 infection, with levels matching or exceeding phage protein, which suggests they are important for efficient phage infection (10).…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Bacteriophage ϕX174 is a small, icosahedral, and non-tailed virus belonging to Microviridae (23) and work has shown that mutations in DnaJ/DnaK/GrpE/GroEL/GroES make the E. coli host more sensitive to lysis by E protein (24). In addition to this work, we have recently shown that the small heat shock proteins (sHsps) IbpA and IbpB were the most upregulated host proteins during ϕX174 infection, with levels matching or exceeding phage protein, which suggests they are important for efficient phage infection (10).…”
Section: Introductionmentioning
confidence: 77%
“…The expression of dCas9 was induced by DAPG (50 µM) at early exponential phase and we allowed 40 min for dCas9 to be produced before phage infection. We did not expect ibpA or ibpB transcripts to be expressed prior to ϕX174 infection because they are within a stress response regulon (10, 12, 56, 57) and we did not subject the cells to temperature-shock. At 60 min post-infection, we found upregulation of both ibpA and ibpB transcripts in the absence of dCas9 expression, whereas the amount of ibpA transcripts were less than 2-fold above non-infected samples, and ibpB transcripts were unchanged when dCas9 was expressed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations